Anthocyanin-rich haskap (Lonicera caerulea L.) berry extracts reduce nitrosamine-induced DNA damage in human normal lung epithelial cells in vitro. (July 2020) - Amararathna, M.; Hoskin, D.W.; Rupasinghe, H.P. Vasantha
Abstract: Diets rich in polyphenols are known to reduce cancer among high-risk populations. Haskap ( Lonicera caerulea L.) berry has abundant phenolic acids and flavonoids, especially anthocyanins. Tobacco-specific nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) present in cigarette smoke, is a major lung carcinogenic factor. We analyzed the efficacy of anthocyanin-rich haskap berry extracts in preventing DNA damage induced by 4-[(acetoxymethyl) nitrosamino]-1-(3-pyridyl)-1-butanone (NNKOAc), a precursor of NKK, in human lung epithelial BEAS-2B cells in vitro . A cocktail of monomeric polyphenols from haskap berries was extracted separately in ethanol and water and profiled. Sub-lethal concentrations of NNKOAc were used to induce DNA damage in BEAS-2B cells, and a cell viability assay was performed to confirm that the tested concentrations of haskap extracts were not cytotoxic to BEAS-2B cells. Cells were pre-treated with the haskap extracts prior to NNKOAc exposure. Dose-dependent DNA damage was observed with carcinogenic NNKOAc, but did not occur in the presence of the haskap extracts. Pre-treatment of the cells with the haskap extracts significantly reduced NNKOAc-induced DNA damage, DNA fragmentation, and intracellular reactive oxygen species and upregulated the ATM-dependent DNA damage repair cascade compared to non-treated BEAS-2B cells. The protective effect of haskap extracts could be related to their polyphenol content and high antioxidant capacity. Highlights: Ethanolic and aqueous haskap berry extracts consist mainly of anthocyanin, cyanidin-3- O -glucoside. The extracts reduced the nitrosamine-induced DNA damage in human normal lung epithelial cells in vitro. Preincubation of cells with the extracts reduced DNA fragmentation and intracellular ROS. The haskap extracts upregulated the ATM-dependent DNA damage repair cascade.